Recent Advances in Jigging Used for Mineral Separation - Chen, Yinghua; Tang, Jie; Li, Haisheng; Chen, Jukai; Cui, Zhe; Xu, Ziyin (Recent Patents on Engineering, 2023)
Background: As a kind of non-renewable natural resource, mineral resources are the important material basis of social development. Mineral resources mined need to be sorted and processed to improve product quality and utilization rate. As an important mineral separation process, jigging has obvious technical advantages and has been widely used in mineral separation technical field. Objective: In this paper, jig related patents are summarized, and their structural characteristics, working principles and technical advantages are analyzed in detail. The research results can provide a meaningful reference for improving mineral separation efficiency and jig technology innovation. Methods: Through the comparative analysis of jig related patents, the current research progress has been summarized, and the future development direction is put forward. Results: The patent is mainly devoted to the external structure transformation and internal flow field optimization of the jig, so as to achieve the purpose of energy saving and high efficiency. Studies have shown that jigging has improved significantly, and many patents have been applied to industrial production practices. Conclusion: Jig has development potential in terms of being large-scale, intelligent, highly efficient, and energy-saving technique, and it can constantly improve the processing ability. Through the intelligent control system to ensure the safe and stable operation of jig, and combined with new materials and structure optimization to improve separation efficiency and working life, jig for mineral separation is of great significance.
Keywords: social development